Boundary layer ozone in the Northern Colorado Front Range in July–August 2014 during FRAPPE and DISCOVER-AQ from vertical profile measurements - S. J. Oltmans (Elementa: Science of the Anthropocene, 2019)
Data from ground-based ozone (O3) vertical profiling platforms operated during the FRAPPE/DISCOVER-AQ campaigns in summer 2014 were used to characterize key processes responsible for establishing O3 profile development in the boundary layer in the Northern Colorado Front Range. Morning mixing from the upper boundary layer and lower free troposphere into the lower boundary layer was the key process establishing the mid-morning boundary layer O3 mixing ratio. Photochemical O3 production throughout the boundary layer builds on the mid-morning profile. From late morning to mid-afternoon the continuing O3 increase was nearly uniform through the depth of the profile measured by the tethersonde (~400 m). Ozonesondes flown on a near daily schedule over a four week period with multiple profiles on a number of days captured the full 1500 to 2000 m vertical extent of O3 enhancements in the mixed boundary layer confirming O3 production throughout the entire boundary layer. Continuous O3 measurements from the Boulder Atmospheric Observatory (BAO) tall tower at 6 m and 300 m showed hourly O3 at the 6 m level ≥75 ppb on 15% of the days. The diurnal variation on these days followed a pattern similar to that seen in the tethersonde profiles. The association of high O3 days at the BAO tower with transport from sectors with intense oil and natural gas production toward the northeast suggests emissions from this industry were an important source of O3 precursors and are crucial in producing peak O3 events in the NCFR. Higher elevation locations to the west of the NCFR plains regularly experience higher O3 values than those in the lower elevation NCFR locations. Exposure of populations in these areas is not captured by the current regulatory network, and likely underestimated in population O3 exposure assessments.